Effectiveness of combined treatment of lanthanum carbonate and hemodialysis for uremic pruritus of skin - WANG You; YU Ye-an; LI Xiang-you; YIN Qing-qiao; XIA Yuan-yu (Linchuang shenzangbing zazhi)
Objective To observe the treatment efficiency of hemodialysis combined with hemoperfusion and oral lanthanum carbonate for uremic pruritus.Methods Twenty-one patients with uremic pruritus attending blood purification room in Wuhan Third Hospital from October 2012 to April 2014 were selected and divided into two groups:A,hemodialysis and hemoperfusion treated group(n= 11),and B,hemodialysis,hemoperfusion and oral lanthanum carbonate treated group(n= 10).The renal function,blood phosphorus,parathyroid pixel and the extent of skin itch were observed and compared before and 8 weeks after treatment.Statistical tests were used to reveal the differences.Results The blood phosphorus levels in both groups were declined significantly after treatment(P<0.01),more significantly in group B than in group A(P<0.01).After treatment,PTH level in group B was significantly lower than in group A(P<0.01).The symptom of skin itch was significantly alleviated in both groups after treatment.The remission rate of treatment in group B was 90%,which was significantly higher than 63.6%in group A(P<0.01).Conclusions The combination of new phosphate binder lanthanum carbonate,hemodialysis and hemoperfusion can more effectively reduce the levels of blood phosphorus and small molecular that can cause skin pruritus,therefore relieve uremic pruritus for therapeutic purposes.